Deformation and tribology of multi-walled hollow nanoparticles - Schwarz, Ulrich S.; Komura, Shigehiro; Safran, Samuel (Arxiv, 2017)
Multi-walled hollow nanoparticles made from tungsten disulphide (WS$_2$) show exceptional tribological performance as additives to liquid lubricants due to effective transfer of low shear strength material onto the sliding surfaces. Using a scaling approach based on continuum elasticity theory for shells and pairwise summation of van der Waals interactions, we show that van der Waals interactions cause strong adhesion to the substrate which favors release of delaminated layers onto the surfaces. For large and thin nanoparticles, van der Waals adhesion can cause considerable deformation and subsequent delamination. For the thick WS$_2$ nanoparticles, deformation due to van der Waals interactions remains small and the main mechanism for delamination is pressure which in fact leads to collapse beyond a critical value. We also discuss the effect of shear flow on deformation and rolling on the substrate.
Gesehen am 18.12.2017